2013
DOI: 10.1007/s13312-013-0277-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of breastmilk of Israeli mothers

Abstract: We conducted this study to determine the fatty acid composition of breastmilk of Israeli women and compare it with baby milk substitutes. Samples of mature breast milk, from 29 lactating Israeli Jewish mothers were collected during feedings. Total milk lipids extracts were transmethylated and analyzed by using an improved gas-chromatographic method. About 72% of the total fatty acids in the investigated breast milk comprised oleic (18:1c; 31±4%), palmitic (16:0; 21±4%), and linoleic (18:2n-6; 20±4%) acids. Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
2
10
1
3
Order By: Relevance
“…29 The FAs composition of mature breast milk of Israeli women was analysed and it was found that the contents of total SFAs, total MUFAs and total PUFAs were 42±7%, 33±5% and 24±4% of total FAs respectively. 30 In a study on Turkish women, Aydın et al showed higher level of SFA in total FAs of breast milk (46.57% at 7 days, 51.56% at 28 days of lactation) than predicted in the control group of current study (44.84±3.93% in colostrum and 44.42±4.72% at 15 days of lactation). 31 Omega-3 supplementation further reduced the values.…”
Section: Discussionsupporting
confidence: 38%
“…29 The FAs composition of mature breast milk of Israeli women was analysed and it was found that the contents of total SFAs, total MUFAs and total PUFAs were 42±7%, 33±5% and 24±4% of total FAs respectively. 30 In a study on Turkish women, Aydın et al showed higher level of SFA in total FAs of breast milk (46.57% at 7 days, 51.56% at 28 days of lactation) than predicted in the control group of current study (44.84±3.93% in colostrum and 44.42±4.72% at 15 days of lactation). 31 Omega-3 supplementation further reduced the values.…”
Section: Discussionsupporting
confidence: 38%
“…A number of individual studies has investigated HMFA composition at specific stages or in particular populations [25][26][27][28][29][30]. Although pooled data analyses exist for selected HMFAs [19,31], macronutrients [32] and amino acids [33], a consolidated HMFA profile based on multiple worldwide studies and reflective of term and preterm milk over the course of lactation is not available yet.…”
mentioning
confidence: 99%
“…Os autores observaram que o LH e o Lacprodan apresentaram perfil semelhante em AGs, com níveis mais elevados de AGs insaturados, quando comparados ao leite de vaca. 51 Em 58 Gardner et al (2017) investigaram se as proporções de AGs no LH mudam em resposta a infecções da mãe e do neonato, através da análise de GC-FID, utilizando-se uma coluna capilar de 0,32 mm de diâmetro interno, revestida com BPX-70. A temperatura do injetor foi de 250 °C e do detector de 300 °C.…”
Section: Cromatogra Ia Em Fase Gasosa (Gc)unclassified